Error Correction Models and Real Convergence - Case of Slovakia - Gavliak, Rudolf; Úradníček, Vladimir; Zimková, Emília (Modele korekcji błędu i rzeczywista konwergencja - przypadek Słowacji, 2009)
On January 1, 2009 the Slovak Republic entered the Economic and Monetary Union. This step is the confirmation that the country has fulfilled nominal criteria for monetary integration. The main aim of the monetary integration is sustainable economic growth and convergence of the real economy to most advanced EU countries. Long lasting mutual trend of analyzed indicators is searched by cointegration. In a short term there might be some deviations which are studied by error correction models (ECM). The output of the contribution is twofold. Firstly we will analyze the long-lasting equilibrium of the real economy, and secondly we will estimate the duration whithin which the searched variables are returning to the longlasting equilibrium in the case of the short-term deviations.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 66, s. 62-71